Event Cosplay Organizer Online dengan Sistem Rekomendasi Juri menggunakan Perbandingan Metode AHP dan SAW (Studi Kasus pada Kaze Production) - Ananda Dhammahito Adhe Herlambang; Julianti Kasih (Maranatha University Press, 2019)
Abstract — As a company that moves and involved inside the creative industry such as pop culture, creating and managing events are the main thing that the company works on. By using website as the media for organizing things related to creating and managing events gives not only the company but also the user as member a big grasp to to big things in such a simple way. Besides all the simple things having an online media also gives the easiest way to access it anywhere and creating a better security from human error.(such as losing document files, damage paperwork, etc.) Having an accessible media could help not only amateur creator starting to create their first event but also on a professional level where they could manage their work to be more organize and safely. Therefore, in this great opportunity doing final assignment will be used to developed the application of 'Sistem Organizer Online Events Cosplay' based on a company Kaze Prodcution. This application will be enchanced with main features like creating schedule for the events, methods score counting for judge recommendation system, and counting the estimation budget for the events. Keywords— cosplay, event, recommendation system, organizer, website.